Enhancing Reading Comprehension through Inspiring Novels: A Pre-Experimental Study in an EFL Context - Mulyarti, Mulyarti (Universitas Muhammadiyah Barru, 2025)
This study investigated the effectiveness of using inspiring novels as instructional media to enhance students’ reading comprehension. A pre-experimental design with one group pre-test and post-test was employed, involving 20 students selected through purposive sampling. Data were collected through reading comprehension tests administered before and after the treatment. The intervention consisted of seven sessions in which students engaged with inspiring novels through group reading and comprehension activities. The findings revealed a significant improvement in students’ reading performance. The mean score increased from 65.5 (SD = 10.50) in the pre-test to 78.5 (SD = 7.45) in the post-test. A paired-samples t-test confirmed that the improvement was statistically significant (t = 10.23, p < .05). Beyond score gains, classroom observations indicated that students were more motivated, demonstrated richer vocabulary acquisition, and actively engaged with the reading materials. These results suggest that inspiring novels are an effective medium for improving reading comprehension in EFL contexts. By combining narrative engagement with structured comprehension tasks, this approach fosters both academic achievement and learner motivation.